The surgical patient prophylaxis of venous thromboembolism - Amaral, Cristina; Tavares, Jorge (Journal of the Portuguese Society of Anesthesiology, 2014)
Anesthesiology’s role of a multidisciplinary responsibility The effectiveness of prophylaxis of venous thromboembolism in surgical patients is demonstrated and has great economic and epidemiological impact. The features and indications in terms of prophylactic therapy should take into account the specific risk factors of the patient, those inherent to the surgery and related to anesthesia itself. Despite the obvious contribution to improving the prognosis, the recommendations of venous thromboembolism prophylaxis in surgical patient is still not fully implemented in hospitals. This relates to various barriers since the lack of recommendations and the difficulty of assessing different degrees of risk and additional risk populations, the fear associated complications, to the still not integrated multidisciplinary responsibility. Furthermore there’s a need to reinforce the importance of execution and registration of process control. The regulators have already implemented programs in order to overcome these barriers, but we are far from a level of excellence across the entire surgical patient. The purpose of this article is to present the latest recommendations for the prevention of venous thromboembolism in surgical patient, including the ninth consensus of the American College of Chest Physicians and the implications for anesthetic management, seeking strategies to overcome some of the barriers to their implementation.